On some boundary problems - Kvedaras, B.; Kibenko , A. V.; Perov, A. I. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. В. Кведарас А. В. Кибенко и А. И. Перов. О некоторых краевых задачах B. V. Kvedaras, A. V. Kibenko ir A. I. Perovas. Apie kai kuriuos kraštinius uždavinius